2017
DOI: 10.1590/1982-02752017000300010
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación del mainstreaming de género en las organizaciones a través de las certificaciones

Abstract: ResumenLas desigualdades entre mujeres y hombres se siguen manteniendo en las organizaciones a pesar de los esfuerzos políticos y sociales realizados para afrontar este fenómeno. Las certificaciones de igualdad son reconocidas en España como uno de los instrumentos políticos diseñados para combatir estos desequilibrios de género a partir de la promulgación de la Ley Orgánica nº 3/2007 para la igualdad efectiva de mujeres y hombres. Este artículo tiene como objetivo identificar el enfoque desde el que las organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Just as an instrumental paradigm prevails in CSR (McWilliams & Siegel, 2011), an instrumental paradigm also seems to prevail when it comes to GE standards. In line with Mimbrero Mallado et al (2017), both public and private entities can be found that promote certifications for commercial purposes, disguised as brands for social progress and equity, without representing transformative progress. A superficial and symbolic use of the concept of GE is observed, most of the times linked to improve the image of organizations more that their commitment to GE or sustainable development.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Just as an instrumental paradigm prevails in CSR (McWilliams & Siegel, 2011), an instrumental paradigm also seems to prevail when it comes to GE standards. In line with Mimbrero Mallado et al (2017), both public and private entities can be found that promote certifications for commercial purposes, disguised as brands for social progress and equity, without representing transformative progress. A superficial and symbolic use of the concept of GE is observed, most of the times linked to improve the image of organizations more that their commitment to GE or sustainable development.…”
Section: Discussionsupporting
confidence: 66%
“…Although women's organizations and women's policy agencies try to challenge the dominant neoliberal framework, they have also been influenced by it and sometimes make use of the BCGE because of its discursive and persuasive power (Kantola & Squires, 2012). GE standards are thus promoted in a way that contributes to fostering the commercial interest of companies rather than to adopting the philosophy of gender mainstreaming (Mimbrero Mallado et al, 2017). The economic benefits eventually take precedence over the more humane ones (Gotsis & Kortezi, 2013); and GE is framed as an economic necessity rather than a matter of social justice, fairness, and human rights (Albrechtsen, 2019; Johansson & Ringblom, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations